Powder X-ray diffraction of 1-(4-aminophenyl)-5, 6-dihydro-3-(4-morpholinyl)-2(1H)-pyridinone, C15H19N3O2. Issue 4 (29th October 2015) - Wang, Qing; Li, Ya Ping; Li, Shan Shan; Tang, Bin; Li, Hui
Abstract : X-ray powder diffraction data for 1-(4-aminophenyl)-5, 6-dihydro-3-(4-morpholinyl)-2(1H)-pyridinone, C15 H19 N3 O2, are reported [ a = 14.877(4) Å, b = 5.893(6) Å, c = 18.984(3) Å, α = 90°, β = 122.298(3)°, γ = 90°, unit-cell volume V = 1406.86 Å 3, Z = 4, and space group P 21 / c ]. All measured lines were indexed and are consistent with the P 21 / c space group. No detectable impurities were observed.